Changes in serum tumor markers in type 2 diabetes mellitus with microalbuminuria - Chen, Lina; Du, Shichun; Li, Yan Bo; Su, Qing; Zhang, Jiangrong; Zhang, Hongmei (Frontiers in Endocrinology, 2023)
Objectives: To investigate changes in serum tumor markers in type 2 diabetes mellitus (T2DM) with microalbuminuria and analyze the relationship between tumor markers and microalbuminuria. Methods: 956 T2DM patients aged 40–70 years hospitalized in the Department of Endocrinology, Xinhua Hospital, China, affiliated with Shanghai Jiaotong University School of Medicine were enrolled from January 2018 to December 2020. The sample comprised 313 T2DM patients with microalbuminuria and 643 T2DM patients with normal urinary microalbumin levels. After assessing the changes in serum tumor markers in T2DM with microalbuminuria, we analyzed the risk of microalbuminuria by serum tumor marker category using multiple logistic regression analysis. Results: Serum CEA, CA199, CA125, CA153, CA211, SCC, CA242, and CA50 levels were significantly higher in T2DM patients with microalbuminuria than in those without microalbuminuria, while serum AFP levels were lower in the microalbuminuria group (P < 0.05). Following adjustment of confounders, serum CEA, CA211, and SCC were independently associated with microalbuminuria in T2DM. An ROC curve was used to estimate the cutoff point of tumor markers for microalbuminuria. Taking the values under the cutoff points as a reference, values for CEA, CA211, and SCC above the cutoff points indicate a significantly high risk of microalbuminuria. The OR of increased CEA for microalbuminuria was 2.006 (95%CI 1.456–2.765), the OR of increased CA211 for microalbuminuria was 1.505 (95%CI 1.092–2.074), and the OR of increased SCC for microalbuminuria was 1.958 (95%CI 1.407–2.724). Conclusion: Several serum tumor markers were related to microalbuminuria in T2DM. Serum tumor markers such as CEA, SCC, and CA211 may indicate early diabetic nephropathy, particularly when elevated in combination. Key words: type 2 diabetes mellitus; tumor markers; microalbuminuria.